2021
DOI: 10.3389/fsurg.2021.607551
|View full text |Cite
|
Sign up to set email alerts
|

A New Precision Minimally Invasive Method of Glial Scar Simulation in the Rat Spinal Cord Using Cryoapplication

Abstract: According to the World Health Organization, every year worldwide up to 500,000 people suffer a spinal cord injury (SCI). Various animal biomodels are essential for searching for novel protocols and therapeutic approaches for SCI treatment. We have developed an original model of post-traumatic spinal cord glial scarring in rats through cryoapplication. With this method the low-temperature liquid nitrogen is used for the cryodestruction of the spinal cord tissue. Forty-five Sprague Dawley (SD) non-linear male ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…We used a previously elaborated model of spinal cord cryoinjury [ 12 , 13 ] characterized by monoplegia of the hind limb, which can last several months ( Figure 1 A). Functional tests showed that intact animals easily reached the preset maximum speed of 50 m/min, whereas the animals with spinal cord injury reached a mean speed of 19 m/min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used a previously elaborated model of spinal cord cryoinjury [ 12 , 13 ] characterized by monoplegia of the hind limb, which can last several months ( Figure 1 A). Functional tests showed that intact animals easily reached the preset maximum speed of 50 m/min, whereas the animals with spinal cord injury reached a mean speed of 19 m/min.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we used a recently proposed rat SCI model accomplished by a controlled cryoapplication. Our technique, unlike other models of traumatic spinal cord injury, consistently reproduces glial scarring and the posttraumatic formation of cysts [ 13 ], which both play a fundamentally negative role against potential neuroregeneration [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study used a modified technique to perform laminectomy, using a motorised dental burr to mechanise the process to refine the process in terms of animal wellbeing, as previously described [ 25 , 85 ]. Even though refined techniques to mechanise laminectomy and reduce bleeding, inflammation and trauma has been adopted by certain researchers [ 86 , 87 ], a majority of publications on the induction of SCI applies the manual, conventional technique to perform laminectomy. So, it is required to replicate this study by performing laminectomy manually to study the effects of analgesia which is also being planned.…”
Section: Discussionmentioning
confidence: 99%